The archaeology of architecture for the knowledge and preservation of the ’modern’ - Pittaluga, Daniela (Restauro Archeologico, 2023)
The aim of this research is to find new tools to know, understand and consequently preserve the most recent architec- tural heritage (20th–21th century). This particularly interesting heritage needs attention, often its state of degradation undermines its conservation. This need is evident not only in the Italian context but also in the western world. The 1972 Unesco Convention defined an initial concept and definition of Heritage, and this concept now became increasingly broader; today, more recent artefacts are now looked upon as elements to be protected, in the same way as older ones. The writer started this research, years ago, currently a close collaboration between DAD Genova and Universidad del Pais Vasco brought more enlightening. The objectives are: verification of the applicability of the tools already adopted in the archaeology of the architecture of traditional constructions and development of the specificities in the interpretation of contemporary constructions.